2018
DOI: 10.1088/1757-899x/374/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Sludge Used as Material for Bricks Fabrication

Abstract: Abstract. Current world trends related to wastewater sludges are: reuse in agriculture, utilization as retaining material for petroleum products or utilization in construction. Bricks from sand-cement or autoclaved cellular concrete are commonly used in construction. The authors propose innovative receipts for bricks and plasters based on textile wastewaters sludge. Centrifuged sludge is mixed with cement to obtain bricks and plaster. For bricks, the mixture is represented by 45% cement and 55% sludge. The pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In the last years, several types of research all over the world have been working on the production of bricks from different waste materials. The following wastes are examples of exciting and suitable additives for bricks production: Kieselguhr sludge et al, (2006), organic residues (Demir, 2008), granite and marble wastes (Dhanapandian and Gnanavel, 2009), spent shea waste (Adazabra et al, 2017a,b), wastewater sludge (Jianu et al, 2018), coal fly ash (Eliche-Quesada et al, 2018), degraded municipal solid waste (Goel and Kalamdhad, 2017), waste glass sludge (Kazmi et al, 2018), cotton soils (Zhang et al, 2013), quarrying wastes (Rukijkanpanich and Thongchai, 2019), bricks kiln dust (Riaz et al, 2019), shale, sewage sludge, coal gangue powder and iron ore tailings (Luo et al, 2020) and electrolytic manganese residue (Li et al, 2020) which are exciting and suitable additives for bricks production.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, several types of research all over the world have been working on the production of bricks from different waste materials. The following wastes are examples of exciting and suitable additives for bricks production: Kieselguhr sludge et al, (2006), organic residues (Demir, 2008), granite and marble wastes (Dhanapandian and Gnanavel, 2009), spent shea waste (Adazabra et al, 2017a,b), wastewater sludge (Jianu et al, 2018), coal fly ash (Eliche-Quesada et al, 2018), degraded municipal solid waste (Goel and Kalamdhad, 2017), waste glass sludge (Kazmi et al, 2018), cotton soils (Zhang et al, 2013), quarrying wastes (Rukijkanpanich and Thongchai, 2019), bricks kiln dust (Riaz et al, 2019), shale, sewage sludge, coal gangue powder and iron ore tailings (Luo et al, 2020) and electrolytic manganese residue (Li et al, 2020) which are exciting and suitable additives for bricks production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous work has shown that in areas with low clay reserves, the amount of clay used in the production of fired bricks can be reduced by using a variety of waste products. These substituted for clay, would improve the properties of fired bricks and come from a variety of sources: agriculture wastes, [3][4][5][6] wastes sludge, [7][8][9] industrial wastes, [10][11][12][13] and mixed wastes. 14 The inter-tropical zone of the globe, which is essentially made up of laterite, 15 is a vast reservoir of raw material for alleviating the problem of the lack of decent, affordable, and sustainable housing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous work has shown that in areas with low clay reserves, the amount of clay used in the production of fired bricks can be reduced by using a variety of waste products. These substituted for clay, would improve the properties of fired bricks and come from a variety of sources: agriculture wastes, 3–6 wastes sludge, 7–9 industrial wastes, 10–13 and mixed wastes 14 …”
Section: Introductionmentioning
confidence: 99%
“…Recycling this waste material and turning it into bricks could reduce the problems of waste disposal while favoring its use in the construction industry (Joo-Hwa 1987;Okuno and Takahashi 1997;Weng et al 2003;Keerthana et al 2019). Researches has been carried out to find an environmental friendly material and method, as well as alternative low cost material for building purposes (Joo-Hwa 1987;Jianu et al 2018;Areias et al 2020;Erdogmus et al 2021;Gencel et al 2021;Limami et al 2021;Minh Trang et al 2021;Zat et al 2021). An important part of global industrial production results in the production of massive quantities of industrial by-products or other solid wastes and the best way to handle the solid waste is through recycling and reusing it into new products (Kioupis et al 2018).…”
Section: Introductionmentioning
confidence: 99%